2015
DOI: 10.4081/cp.2015.749
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrobasilar Dolichoectasia Induced Hydrocephalus: The Water-Hammer Effect

Abstract: Vertebrobasilar dolichoectasia is a clinical entity associated rarely with obstructive hydrocephalus. We present a 48-year old male with a profound dilatation of the ventricular system due to a dolichoectatic basilar artery, as appeared in imaging studies. The patient suffered from longstanding hydrocephalus and presenile dementia. The underlying mechanism for obstructive hydrocephalus due to vertebrobasilar dolichoectasia is considered to be both a water-hammer effect and a direct compression of adjacent stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Other possible symptoms of basilar tortuosity include hydrocephalus and ischemia due to compression of the third ventricle and mass effect on adjacent structures, respectively [11]. This mass effect can lead to obstructive hydrocephalus, which may present as cognitive impairment [12]. As both of the patients presented in this report had notable enlargement of CSF collection spaces, we must acknowledge the possibility that the vascular malformations may be contributing to their cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…Other possible symptoms of basilar tortuosity include hydrocephalus and ischemia due to compression of the third ventricle and mass effect on adjacent structures, respectively [11]. This mass effect can lead to obstructive hydrocephalus, which may present as cognitive impairment [12]. As both of the patients presented in this report had notable enlargement of CSF collection spaces, we must acknowledge the possibility that the vascular malformations may be contributing to their cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…in their study suggested that the underlying mechanism for obstructive hydrocephalus due to vertebrobasilar dolichoectasia are both a water-hammer effect and a direct compression of adjacent structures. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…It is predominantly due to cerebrospinal fluid (CSF) circulation disorders caused by direct or indirect compression of the bottom of the third ventricle or midbrain aqueduct. [ 2 7 10 12 17 26 ] It is assumed that obstructive-visible hydrocephalus in VBD is a result of compression of the foramen of Monro, the cerebral aqueduct, or the third ventricle. [ 26 ] However, some other studies declare a different mechanism for obstructive-invisible hydrocephalus; that is, a combination of increased CSF pulse pressure and impairment of outward CSF flow by counter current pulsations of the basilar artery.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 7 10 12 17 26 ] It is assumed that obstructive-visible hydrocephalus in VBD is a result of compression of the foramen of Monro, the cerebral aqueduct, or the third ventricle. [ 26 ] However, some other studies declare a different mechanism for obstructive-invisible hydrocephalus; that is, a combination of increased CSF pulse pressure and impairment of outward CSF flow by counter current pulsations of the basilar artery. The proposed mechanism for obstruction-invisible hydrocephalus is a “water hammer” effect within the bottom of the third ventricle or foramina of Monro, which is generated by pulsatile blood flow in the dolichoectatic arteries and results in hydrocephalus under normal pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation